O percurso gerativo de sentido aplicado à análise documental de textos narrativos de ficção: perspectivas de utilização em bibliotecas universitárias - Antonio, Deise Maria [UNESP] (2008)
The works of fiction have no tools for appropriate subject analysis due to the absence of methodological procedures that contribute effectively to the treatment of this kind of document to the establishment of the theme. Thus, it is proposed to search for subsidies in the gerativo theoretical and methodological journey in a sense, part of Discursive Semantic for understanding and extracting the theme in works of fiction. The objectives of the research are the analysis, identification and methodological application of the route, seeking to identify those figurative and thematic texts as well as the implementation of the meaning of the text, the study of the actors that permeate the sequence of figures and topics, determining the relationship in that kind of superstructure narrative, identify and analyze the level of experience in the professional performance of librarians in the activity Index of works of fiction, identifying and analyzing the attitudes of professional librarians in relation to the activity of indexing and the offering theoretical basis studies for future studies that put into effect that a methodological proposal for identifying the subject of fictional works. The chosen method to carry out the research is the descriptive search that allows the observation, the registration, examination and the correlation of facts. The structured and focused interview will be used as a technique for collecting data that will allow comparison and reflection of the answers. The thematic and figurative journey will be applied and analysed in short stories for the establishment of the theme (Phase 1). The collection of data was held in three libraries of UNESP Libraries Network in order to extract the techniques used by librarians to identify the topic of fictional documents (Stage 2). The final phase includes the transcription and analysis of results and reflection enabling guidelines for the analysis of documentary works fictional.